The DEVELOPMENT OF A VALIDATED STABILITY INDICATING LC-MS METHOD FOR THE DETERMINATION OF TENOFOVIR DISOPROXIL FUMARATE USING QUALITY BY DESIGN APPROACH - SAHA, CHANDNI; GUPTA, N. VISHAL; CHANDAN, R. S.; P., SHANMUKHA PRIYA (International Journal of Applied Pharmaceutics, 2019)
Objective: To develop a validated Liquid Chromatography-Mass Spectrometry (LC-MS) method through Quality by Design (QbD) approach for the determination of tenofovir disoproxil fumarate (tenofovir DF) in bulk, pharmaceutical formulation and stress conditions. Methods: The analytical target profile (ATP) was to develop a simple, accurate, precise, specific, and robust method with the Critical Quality Attribute (CQA) being retention time, theoretical plate and peak tailing. Derived from the risk assessment studies, four high-risk factors were screened using resolution V irregular fraction design. Organic modifier strength, flow rate and injection volume were further optimized using Box-Behnken design (BBD). The optimized method condition was validated and applied for the determination of the analyte in pharmaceutical formulation. The stability of the analyte in stress conditions was determined. All experiments were performed using reverse-phase Acquity UPLC BEH C18 (1.7 µm, 1 mm X 50 mm) column coupled in-line with Synapt G2 mass spectrometer in positive electrospray ionization (ESI) mode with electron multiplier analog-to-digital detector. Results: Optimized method condition eluted analyte at 3.40 min and the m/z 520 ratified the analyte peak. The method was validated and was found to be specific, linear in the range of 20-100 µg/ml (R2 = 0.9998) with accuracy between 98.71% - 101.17% and precise. The limit of detection and quantification were 5.50 µg/ml and 16.68 µg/ml respectively. Analyte degraded completely in acid and basic environment, however, stable in oxidative and photolytic conditions. Conclusion: The validated method developed through the systematic and rational QbD approach bespoke superior quality. The QbD approach not only justified the entire process but also eliminated uncertainties.